High reinforcing value of food is related to slow habituation to food. (August 2020) - Epstein, Leonard H.; Carr, Katelyn A.; O'Brien, Alexis; Paluch, Rocco A.; Temple, Jennifer L.
Abstract: Background: The rate of habituation to food and reinforcing value of food are processes that are related to food intake and body weight. Reinforcing value of food provides an index of the motivation to eat, while habituation provides an index on how repeated presentations of food relate to reduced behavioral and physiological responses to that food. Objective: To investigate the relationship between habituation phenotypes to salty, sweet and savory foods and reinforcing value of those foods. Design: A sample of 229 8–12-year-old children at risk for obesity completed reinforcing value and habituation tasks for foods that varied in savory, sweet or salty tastes. Multivariate Group Based Trajectory Modeling was used to create four unique patterns of habitation to foods based on detailed 10 s epochs of responding for food over a 24 min task. Differences in reinforcing value of food were assessed for these habituation phenotypes. Results: Results showed a graded relationship between the overall habituation phenotypes and reinforcing value of food, as those with the relatively flat habituation phenotype found food more reinforcing than those with phenotypes that showed rapidly decelerating responding across all taste categories. Conclusions: Those who habituated slower found food more reinforcing than those with a rapid habituation phenotype. Implications of these phenotypes for understanding how habituation relates to food intake are discussed. Highlights: Habituation and reinforcing value of food are related to energy intake and body weight. Habituation phenotypes can be characterized by the pattern of responding. Four habituation phenotypes range from rapidly decelerating to relatively flat responding. Reinforcing value of food was greater for flat than rapidly decelerating phenotypes. Results were consistent across salty, sweet and savory taste groups